REACT Contextual Approach: Effective Numeracy Teaching for Future Mathematics Teachers - Wulandari, Shinta; Kusuma, Arief Ertha; Ridwan, Ridwan; Suciati, Suciati; Rusmansyah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study describes adequate numeracy learning in schools for future mathematics teachers in North Kalimantan. It involved 30 students as respondents who observed numeracy teaching carried out by local facilitator teachers in Bunyu district, North Kalimantan. The researcher utilized the REACT contextual approach to offer practical experience in school numeracy teaching. The respondents, assuming the role of students receiving numeracy instruction, observed the teaching process, filled out questionnaires, and provided feedback on the activities through interviews. We used mode score analysis and synthesis of interview results to analyze the student response data descriptively and quantitatively. The results showed that students who attended lectures with the REACT contextual approach strategy responded positively with a response mode score of 4, which is in the excellent category. The interview results showed a clear positive response from most students after participating in the activity. The students expressed that the lecturer's new strategy helped them acquire knowledge and achieve lecture objectives. Therefore, the application of the REACT contextual approach in innovative learning model lectures on effective numeracy teaching for future mathematics teachers in North Kalimantan has proven highly effective.